2021
DOI: 10.1093/schbul/sbaa199
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Specific Childhood Adversities and Symptom Dimensions in People With Psychosis: Systematic Review and Meta-Analysis

Abstract: Despite the accepted link between childhood abuse and positive psychotic symptoms, findings between other adversities, such as neglect, and the remaining dimensions in people with psychosis have been inconsistent, with evidence not yet reviewed quantitatively. The aim of this study was to systematically examine quantitatively the association between broadly defined childhood adversity (CA), abuse (sexual/physical/emotional), and neglect (physical/emotional) subtypes, with positive, negative, depressive, manic,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
30
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(38 citation statements)
references
References 43 publications
4
30
1
Order By: Relevance
“…Although it is unclear why no group difference was observed during the first months following psychosis onset, these data suggest that male EPP reporting a first PSA before 12 years old are prone to anxiety. We found however no effect of PSA on any of the other psychopathological dimensions, despite a weak association between positive symptoms and physical or sexual abuse revealed by a meta-analysis in people with psychosis [ 8 ]. Explanation for this apparent discrepancy may include the relatively small size of our cohort, but also the fact that the meta-analysis considered both sexes and PSA until age of 18 years regardless of the time of exposure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although it is unclear why no group difference was observed during the first months following psychosis onset, these data suggest that male EPP reporting a first PSA before 12 years old are prone to anxiety. We found however no effect of PSA on any of the other psychopathological dimensions, despite a weak association between positive symptoms and physical or sexual abuse revealed by a meta-analysis in people with psychosis [ 8 ]. Explanation for this apparent discrepancy may include the relatively small size of our cohort, but also the fact that the meta-analysis considered both sexes and PSA until age of 18 years regardless of the time of exposure.…”
Section: Discussionmentioning
confidence: 99%
“…Some forms of severe abuses with first exposure before 12 years old have the most robust association with poor functional outcome [ 5 ]. Thus, increasing evidence suggests that the time at first exposure to trauma, but also the type of traumatic/adverse experiences determine their impact on later outcome [ 8 11 ]. Moreover, studies report either additive or synergistic interactions between CT and polygenetic risk score for schizophrenia [ 12 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the outcomes are often considered as SCZ, or MDD or even major psychoses (combining SCZ & BD), which are extremely heterogeneous entities, involving microphenotypes (Maj et al, 2021), and which accordingly may have very different biological underpinnings. Evidence is showing that there are some levels of specificity between adversity subtypes and symptoms domains, for example, abuse is more related to positive symptoms while neglect is not (Alameda et al, 2021) and that CU is associated with paranoia (Freeman et al, 2005). Thus, using a composite measure of CA and broadly defined conditions when trying to understand specific mediating epigenetic pathways may consider such specific links between environment and psychopathology first.…”
Section: Summary and Outstanding Questionsmentioning
confidence: 99%
“…Findings from previous research reported that those with a history of sexual abuse are at risk of developing disturbances involving emotion regulation, interpersonal relationships, and self-concept, which are considered essential pieces of criteria for ‘complex PTSD’ (World Health Organization, 2019 ). In support of the affective pathway to psychosis, most research demonstrated that CSA was connected to the positive and negative symptoms of psychosis through symptoms of general psychopathology (Alameda, 2021 ; Bloomfield, 2021 ). These findings underline the potential utility of examining the interactions between psychosis and PTSD (Hardy et al, 2021 ; Isvoranu, 2017 ; Liotti & Gumley, 2008 ).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, increasing evidence from large population-based and prospective studies supports the notion of a causal relationship between the experience of CSA and psychosis risk (Fisher, 2013 ; Misiak, 2017 ). Growing meta-analytical research also accentuated the associations between developmental trauma and psychosis via PTSD, dissociation, and emotional dysregulation (Alameda, 2021 ; Bloomfield, 2021 ; Matheson et al, 2013 ; Varese, 2012 ). Childhood trauma, such as sexual abuse, has been shown to be associated with more severe clinical psychotic symptoms and consistently higher severity of both psychotic experiences and symptoms over time (Garcia, 2016 ; Trotta et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%